A Case of First Branchial Cleft Fistula Presenting with an External Opening on the Root of the Helical Crus - Sung Il Cho (Case Reports in Medicine)
Background. First branchial cleft anomalies (FBCA) are rare clinical entities of the head and neck. Typically, the tract of the FBCA begins in the external auditory canal and ends in the postauricular or submandibular region. Case Presentation. We present a case of a 23-year-old man who had a first branchial cleft fistula with atypical opening on the root of the helical crus. Complete excision of the tract, including the cuff of surrounding cartilage, was performed. Histopathology revealed a fistular tract lined with squamous epithelium. To our knowledge, this is the first case to be reported of type I FBCA with an opening on the root of the helical crus. The low incidence and varied presentation often result in misdiagnosis and inappropriate treatment. Conclusions. In the patients with FBCA, careful recognition of atypical variants is essential for complete excision.